Evaluation of Clinical Supervision Model to Improve Pedagogical Competence of Elementary School Teachers - Sinaga, Ester Justina; Nasrun, Nasrun; Lubis, Wildansyah (Randwick International of Education and Linguistics Science Journal, 2024)
This study aims to evaluate a clinical supervision implementation model of the PEDAGOSUP-based clinical supervision model in improving the pedagogical competence of elementary school teachers at the Santa Lusia Virgini Foundation, Pematangsiantar, with a focus on the model developed meeting the standards of feasibility, practicality, and effectiveness for use. The type of research used in this study is R&D (Research and Development). Model development refers to the ADDIE research and development model with the stages of Analysis, Design, Development, Implementation, Evaluation. The subjects of this study were 50 elementary school teachers at the Santa Lusia Virgini Foundation, Pematangsiantar. The research location was carried out in 3 elementary school units under the auspices of the Santa Lusia Virgini Foundation, Pematangsiantar, namely Santa Lusia Sei Rotan Elementary School, Santa Lusia Siborongborong Elementary School, and Santa Maria Dolok Sanggul Elementary School. The result show that the supervision program has increased the pedagogical competence of teachers in cycles I, II, and III by 37.50%; 62.50%; and 100.00%, respectively. That implementation of clinical supervision is effective and can improve the pedagogical competence of teachers at the Santa Lusia Virgini Foundation